Tinjauan Pustaka Systematik: Pengaruh Kecemasan Matematika Terhadap Kemampuan Pemecahan Masalah Siswa - Setiawan, Makis; Pujiastuti, Emi; Susilo, Bambang Eko (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
Mathematics anxiety will cause students to become depressed during mathematics learning. This results in students not being able to receive and understand the lesson well. The next thing that happens is that students' solving abilities cannot develop and eventually their learning outcomes become less complete. The purpose of this study was to analyze the effect of mathematics anxiety on students' problem solving abilities. This study uses the SLR (Systematic Literature Review) method. The result of this research is the effect of math anxiety on problem solving ability is negative. Based on the studies reviewed, it can be concluded that the high level of students' mathematics anxiety means that the problem solving ability produced is low, and vice versa. Problem solving ability is strongly influenced by students' mathematical anxiety. Then the math anxiety arises, one of the causes is that students are less able to understand the concept of the material presented. So as a teacher or teacher, the first thing to fix is ​​to instill in students not to be afraid of mathematics, because mathematics is not as difficult as imagined.